2018
DOI: 10.1007/s13691-018-0333-2
|View full text |Cite
|
Sign up to set email alerts
|

A case of uterine carcinosarcoma which was strongly suspected to have metastases to the psoas and gluteus muscles

Abstract: Metastasis to the skeletal muscles is uncommon. We report a case which was strongly suspected to have psoas and gluteus muscle metastases from uterine carcinosarcoma. A 68-year-old woman (gravida, 2; para, 0) underwent retroperitoneal endoscopic paraaortic lymphadenectomy, laparoscopic modified radical hysterectomy, bilateral salpingo-oophorectomy and pelvic lymphadenectomy for uterine carcinosarcoma, suspected to be stage IB. Metastasis to one right pelvic lymph node was observed. Ascites fluid cytology was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…5 By contrast, we reviewed 2 case reports of good outcomes after resection of solitary muscle metastases from cervical cancer. 6,13 In conclusion, we report an interesting and unusual case of CRC metastasizing to the left psoas muscle initially diagnosed as a cystic lesion. Unlike other adenocarcinomas of the rectosigmoid junction, which normally metastasize to the liver or bone.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…5 By contrast, we reviewed 2 case reports of good outcomes after resection of solitary muscle metastases from cervical cancer. 6,13 In conclusion, we report an interesting and unusual case of CRC metastasizing to the left psoas muscle initially diagnosed as a cystic lesion. Unlike other adenocarcinomas of the rectosigmoid junction, which normally metastasize to the liver or bone.…”
Section: Discussionmentioning
confidence: 79%
“…5 Another review of 52 patients with skeletal muscle metastases showed that the most commonly affected muscles are gluteus, psoas, and erector spinae. 6 According to a database from the Japanese Registry of Autopsies, the incidence of skeletal muscle metastases is 0.028%. 5 Other authors consider the prevalence of them between 0.03% and 5.6%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Musculoskeletal metastasis of gynecological cancers has been described in women mostly with cancer of the cervix and the psoas muscle is the most common site of metastasis ( Ishidera et al, 2018 ). Uterine cancer metastasis has been theorized to commonly include parametria, pelvic and paraaortic lymph nodes and less commonly the lungs, liver, bones and brain.…”
Section: Discussionmentioning
confidence: 99%